Electrical and electrochemical behavior of [bmim][DCA] + γ-butyrolactone electrolyte. (October 2016) - Zec, Nebojša; Bešter-Rogač, Marija; Marolt, Gregor; Vraneš, Milan; Gadžurić, Slobodan
Highlights: Electrical conductivity of the mixture reaches maximum at x IL ≈ 0.2. [bmim][DCA] has 50% lower conductivity comparing to [emim][DCA]. Addition of GBL increases ionicity of the mixture. GBL does not reduce electrochemical stability of the mixture. [bmim][DCA] exhibits a potential window of 3.70 V. Abstract: Electrochemical and transport properties of the pure 1-butyl-3-methylimidazolium dicyanamide ionic liquid, [bmim][DCA], and its binary liquid mixtures with γ-butyrolactone (GBL) were studied at temperatures from (273.15 to 323.15) K at atmospheric pressure over the whole composition range. Electrical conductivity data were correlated using Arrhenius, Casteel–Amis and Vogel–Tammann–Fulcher equations. Several semi-empirical models (quasi-Arrhenius and Bahe–Varela model) were also tested. Electrochemical stability of [bmim][DCA] + GBL was also investigated. It was found that addition of GBL do not reduce electrochemical stability of investigated solution. All the results obtained for [bmim][DCA] + GBL are compared with those reported for binary mixtures of GBL and ionic liquids with dicyanamide, [DCA] −, and bis(trifluoromethylsulfonyl)imide, [TFSI] −, anions. At the compositions where maximum of conductivity is observed, difference in conductivity between [DCA] − and [TFSI] − based ionic liquids + GBL mixtures is around 70%. It was found that type of the cation (imidazolium and pyrrolidinium) do not influence the electrical conductivity of the mixture.